Using Information and Communication Technologies to Prevent Suicide Among Secondary School Students in Two Regions of Chile: A Randomized Controlled Trial - Mascayano, Franco; Schilling, Sara; Tapia, Eric; Santander, Felipe; Burrone, María S.; Yang, Lawrence H.; Alvarado, Rubén (Frontiers in Psychiatry, 2018)
Background: There is an increasing concern for addressing suicide among adolescents in Latin America. Recent mental health policies encourage the development and implementation of preventive interventions for suicide. Such initiatives, however, have been scarcely developed, even in countries with solid mental health services such as Chile. The use of information and communications technology might contribute to create accessible, engaging and innovative platforms to promote well-being and support for adolescents with mental health needs and suicide risk. Objective: To evaluate a program based on information and communications technology to prevent suicide and enhance mental health among adolescents in Chile. Method: A cluster randomized controlled trial will be conducted including 428 high-school students aged 18-14 years in two regions of Chile. Study procedures will take place as follows: 1) design of the intervention model and creation of prototype; 2) selection and randomization of the participating public schools; 3) implementation of the 3-month intervention and evaluation at baseline, post-intervention period, and a 2-month follow-up. Suicidal ideation at the 2-month follow up is the primary outcome in this study. Secondary outcomes include negative psychological outcomes (e.g., stigma, depression, anxiety) as well as a number of protective psychological and social factors. Indicators regarding the study implementation will be also gathered. Discussion: Here we describe a novel program based on technological devices and aimed to target youth suicide in Chile. This is the first clinical trial of such a program in Latin America, and to our knowledge, the first of its kind in any middle income country.